Combining First Nations Research Methods with a World Health Organization Guide to Understand Low Childhood Immunisation Coverage in Children in Tamworth, Australia - Thomas, Susan; Allan, Natalie; Taylor, Paula; McGrady, Carla; Bolsewicz, Kasia; Islam, Fakhrul; Cashman, Patrick; Durrheim, David; Creighton, Amy (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
In Australia, we used the World Health Organization’s Tailoring Immunization Programmes to identify areas of low immunisation coverage in First Nations children. The qualitative study was led by First Nations researchers using a strength-based approach. In 2019, Tamworth had 179 (23%) children who were overdue for immunisations. Yarning sessions were conducted with 50 parents and health providers. Themes that emerged from this research included: (a) Cultural safety in immunisation services provides a supportive place for families, (b) Service access could be improved by removing physical and cost barriers, (c) Positive stories promote immunisation confidence among parents, (d) Immunisation data can be used to increase coverage rates for First Nations children. Knowledge of these factors and their impact on families helps ensure services are flexible and culturally safe.